Overlapping Analysis of People's Housing Savings Program (Tapera) and Additional Service Benefits (MLT) According to Legal Perspective in Indonesia - Windari Windari; Sapto Hermawan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The Public Housing Savings Program or what is known as Tapera has become a national polemic which is starting to become unsettling among the Indonesian people. The People's Housing Savings Management Agency (BP Tapera), which until now seems to only collect public funds through savings with a savings scheme that is still unclear. By looking at this problem, the author found that the Additional Service Benefits program that previously existed and could run exactly the same as the Tapera program with income tax cuts for each taxpayer, this shows that it would be more effective if there was just one program so that there would be no inequality. According to the Minister of Manpower's Regulation regarding the procedures for granting, requirements and types of additional service benefits, it is stated that the type of additional service benefit can be in the form of a housing mortgage, which to date not all people use.